The Persuasive Techniques of Anomali Coffee Advertisements on Instagram Posts - Syahriati Syahriati; Andi Ernie Zaenab Musa; Andi Rustan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores the persuasive linguistic techniques used in 50 Instagram advertisements by Anomali Coffee, a prominent Indonesian specialty coffee brand. The research aims to identify and analyze the linguistic strategies embedded in captions, hashtags, slogans, and textual elements in promotional visuals using Lamb’s (2011) 21 category persuasive language framework. A descriptive qualitative approach was adopted for this purpose. The analysis reveals 46 instances of persuasive techniques, with the most common being inclusive language, imagery, hyperbole, connotation, and colloquial expressions. These findings suggest that Anomali Coffee strategically employs emotional engagement, community oriented language, and sensory appeals to strengthen brand identity and resonance. Additionally, credibility enhancing strategies such as expert opinion and evidence are also evident. The study contributes to the application of Lamb’s taxonomy in Indonesian digital marketing, particularly in the specialty coffee industry, showing how linguistic persuasion can amplify consumer interaction on social media platforms. However, the study’s focus on a single brand and textual features limits its generalizability. Future research should consider cross brand comparisons, multimodal analyses, and consumer response studies to further explore the effectiveness of persuasive techniques. Overall, the findings offer valuable insights into the role of persuasive language in shaping digital marketing strategies for local coffee brands in Indonesia.